ATHLETIQUE: interest of an adapted physical activity program in patients with juvenile idiopathic arthritis: a feasibility and preliminary effectiveness study - Py, Stéphanie; Maylié, Florine; Parmentier, Anne-Laure; Vidal, Chrystelle; Cuinet, Benjamin; Mauny, Fréderic; Lohse, Anne; Toussirot, Eric; Yoshimasa, Sagawa; Tordi, Nicolas; Binda, Delphine; Ballot-Schmit, Claire (Frontiers in Immunology, 2023)
Background: Juvenile Idiopathic Arthritis (JIA) is associated with joint inflammation, pain and limited joint mobility, impacting the practice of physical activities. Adapted Physical Activities (APA) are an increasingly used method of rehabilitation, but additional studies are needed to Discussion: This study will be conducted in the short and medium-term, with one-year follow-up, including 3 months of APA sessions for the experimental group. The sessions proposed during the APA program will mainly be aerobic and bodyweight exercises. Furthermore, in contrast to previous studies on this topic, our study will integrate a novel element, namely the use of a pedometer watch. This watch will help to implement strategies to address motivation. This study aims to improve physical and mental well-being, provide a basis for the design of a larger study, and propose recommendations adapted to children with JIA.Trial registration: Registered with ClinicalTrials.gov under the number NCT05572424